Variation in Annual Ring and Wood Anatomy of Six Tree Mangrove Species in the Nicoya Gulf of Costa Rica - Torres-Gómez, Danilo; Cifuentes-Jara, Miguel (MDPI, 2025)
There is limited information regarding the adaptation of anatomical features and growth ring formation to ecological site conditions in Costa Rican mangrove trees. We used the methods and principles of ecological anatomy to explore the relationship between wood properties (e.g., ring formation, anatomical characteristics) and ecological factors for six mangrove tree species growing in three sites in the Gulf of Nicoya in Costa Rica. We found that variations of ecological conditions affected the growth ring formation of Avicennia bicolor, Avicennia germinans, Pelliciera rhizophorae and two species of Rhizophora but not Laguncularia racemosa. Site conditions affected the anatomical features of the mangrove tree species. Ray dimensions (height and width) were the factors most affected, which were followed by the frequency, diameter, and length of vessels. The fiber dimensions, green density, specific gravity, and carbon content were also affected by the site conditions. The plasticity in ray (increasing of ray dimension) and vessel elements (multiple vessels) facilitate efficient hydraulic conductivity amidst negative growth conditions and physiological restrictions for mangrove trees. We hypothesize that soil salinity, freshwater inputs and intertidal flooding influence these changes. Laguncularia racemosa presented the most changes in anatomical features across the different sites, followed by Pelliciera rhizophorae, with identical changes between Avicennia and Rhizophora spp. Finally, site salinity and wave energy affected the highest number of anatomical changes in mangrove tree species, including 38 changes in the wood structures in site 1.